An Assessment of the Human Resources, Skills Training and Business Services in Timor Leste - Callander, John W. (World Bank, Washington, DC, 2013)
This report analyses the business training and business services sectors in Timor Leste, and recommends a number of initiatives for the strengthening of these important sectors of the economy. Small, Medium Size Enterprises (SMEs) have had limited access to information, and there seems to be a lack of understanding and entrepreneurial discipline. Entrepreneurs need to be more aware of the necessity of generating a cashflow in order to monitor economic activity, and keep a business solvent. This shortcoming is linked to cultural characteristics, but it is compounded by a historical reliance upon government. As enterprises learn from their mistakes, they are becoming more self-reliant. New enterprises understand that survival and success is based upon entrepreneurial discipline and a clear understanding of market forces.